Negative Differential Resistance: Double Negative Differential Resistance Device Based on Hafnium Disulfide/Pentacene Hybrid Structure (Adv. Sci. 19/2020). Issue 19 (7th October 2020) - Jung, Kil‐Su; Heo, Keun; Kim, Min‐Je; Andreev, Maksim; Seo, Seunghwan; Kim, Jin‐Ok; Lim, Ji‐Hye; Kim, Kwan‐Ho; Kim, Sungho; Kim, Ki Seok; Yeom, Geun Yong; Cho, Jeong Ho; et al.
Abstract : In article number 2000991, Jeong Ho Cho, Jin‐Hong Park, and co‐workers report a double negative differential resistance (D‐NDR) characteristic of a hybrid 2D van der Waals (2D vdW)/organic tunneling device consisting of a hafnium disulfide/pentacene heterojunction and a 3D pentacene resistor. This D‐NDR device technology based on a hybrid 2D vdW/organic heterostructure provides a scientific foundation for various circuit applications that require the NDR phenomenon.